IDENTIFIKASI DALAM PROSES PENYIAPAN OBAT PASIEN DI UNIT RAWAT INAP RUMAH SAKIT X: MENGAPA TIDAK PATUH? - Alberti Shintya Sari; Mariani Indahri; Eriko Prawestiningtyas (Jurnal Administrasi Publik, 2024)
Indentification in the Patient’s Medication Preparation Process in the Inpatient Unit of Hospital X: Why Not Complience?. Some nurses cannot implement identification during medicine preparation in the ward although hospital accreditation was performed. This research aims to identify possible causes of why identification during medicine preparation is not fully implemented. Data was collected through questionnaires and interviews with attending nurses and analyzed with a fishbone diagram and 5 whys to get the root cause. The most often overlooked process is providing the patient’s identity on their medication box in the nurse station. A system that could ensure each box had the patient’s identity and simplify the process needs to be developed.